A rapid capillary electrophoresis method with LED-induced native fluorescence detection for the analysis of cannabinoids in oral fluid1. Issue 18 (21st September 2015) - Mazina, Jekaterina; Spiljova, Anastassija; Vaher, Merike; Kaljurand, Mihkel; Kulp, Maria
<x xml:space="preserve">Abstract</x> In the present study, a capillary electrophoresis method with native fluorescence detection for the quantification of two main marijuana cannabinoids, tetrahydrocannabinol (THC) and cannabidiol (CBD), in oral fluid is described.